Does Theory of Planned Behavior Explain the Link Between Memorable Tourist Experience and Revisit Intention? A Halal Tourism Perspective - Abror, Abror; Patrisia, Dina; Engriani, Yunita; Linda, Muthia Roza; Mulyani, Erly; Firman, Firman; Anuar, Marhana Mohamed; Saputra, Jumadil (International Review of Management and Marketing, 2025)
This study aims to examine the link between memorable tourist experience and revisit intention. The study extended the theory of planned behavior (TPB) in the context of halal tourism. This quantitative survey used 500 Muslim tourists who visited West Sumatra as the respondents. It employed structural equation model with Partial Least Square (PLS) as the data analysis tool. This research found that memorable tourist experience has a significant impact on revisit intention through TPB dimensions, including attitude, subjective norm and perceived behavioral control as the mediators. This study also found that tourist happiness has a significant impact on revisit intention. It contributed to extending the TPB in the halal tourism context which led to the revisit intention. In addition, some limitations and future research are discussed.